Electrocatalytic electrode for high-salt high-ammonia-nitrogen wastewater treatment and application thereof
Patent Information
- Application Number
- CN202511555592.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-10-29
AI Technical Summary
该电解过程是在强酸高盐条件下,不仅消耗大量酸而且还提高了废水的盐分,而长期在高盐强酸环境中运行易导致电极材料腐蚀,同时也会导致活性涂层剥落,缩短了电极使用寿命
[0034]与现有技术相比,本发明的有益效果体现在:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to a corrosion-resistant, highly active composite electrocatalytic electrode suitable for high salinity (Cl... - Highly efficient degradation of industrial wastewater with concentrations > 5000 mg / L and high ammonia nitrogen (NH4-N > 200 mg / L). Background Technology
[0002] Industrial production, especially in coastal refining and chemical enterprises, generates wastewater containing high concentrations of salt and ammonia nitrogen. If this wastewater is discharged directly without effective treatment, it will cause serious environmental pollution, leading to eutrophication of water bodies, disrupting ecosystem balance, and posing a threat to human health. Traditional biological methods suffer from microbial inactivation in high-salt environments, while physicochemical methods (such as stripping and breakpoint chlorination) suffer from low treatment efficiency, high energy consumption, and secondary pollution.
[0003] Electrocatalysis, as an advanced oxidation technology, has demonstrated enormous potential and unique advantages in the treatment of recalcitrant industrial wastewater. With its strong oxidizing capacity, environmental compatibility, and operational controllability, it has become a powerful tool for solving complex water pollution problems. However, existing electrocatalytic electrodes have limited corrosion resistance; long-term operation in high-salt, high-ammonia-nitrogen environments easily leads to electrode material corrosion, shortening electrode lifespan. Surface contamination and passivation also severely affect catalytic efficiency and stability, limiting their application in the treatment of high-salt, high-ammonia-nitrogen wastewater. Therefore, developing a corrosion-resistant, highly active electrocatalytic electrode has become an urgent problem to be solved in addressing the challenges of treating high-salt, high-ammonia-nitrogen wastewater.
[0004] Patent document CN 119591204A discloses "An electrode material for electrocatalytic degradation of organic wastewater containing high concentrations of nitrate and its application." This method describes the preparation of an electrode material for degrading organic wastewater containing high concentrations of nitrate. It uses a Ti / Cu-Sn cathode and a metal electrode as the anode to construct an electrolytic cell for electrolytic denitrification of organic wastewater containing high concentrations of nitrate. At the anode, chloride ions oxidize the ammonia nitrogen generated from nitrate degradation into nitrogen gas through oxidation. Simultaneously, nitrate is removed at the cathode and hydrogen gas is produced, while organic matter is removed at the anode. This electrolysis process operates under strong acid and high salinity conditions, consuming large amounts of acid and increasing the salinity of the wastewater. Long-term operation in a high-salt, strong-acid environment easily leads to corrosion of the electrode material and peeling of the active coating, shortening the electrode's lifespan.
[0005] To address the problems of harsh reaction conditions and easy electrode corrosion in electrocatalytic oxidation technology, this invention provides an electrocatalytic electrode for the treatment of high-salt and high-ammonia-nitrogen wastewater and its application. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing an electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater and its application. This electrocatalytic electrode exhibits excellent corrosion resistance and electrocatalytic activity, effectively promoting the decomposition and transformation of pollutants in high-salt, high-ammonia-nitrogen wastewater, significantly reducing the salt and ammonia-nitrogen content. Furthermore, the application method is simple, requiring no acid or alkali adjustment, and is easy to operate. It also exhibits strong resistance to shock loads and is suitable for treating various types of high-salt, high-ammonia-nitrogen wastewater, thus achieving broad market application prospects.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] The electrocatalytic electrode for treating high-salt and high-ammonia-nitrogen wastewater of the present invention is a TiN / SiO2 / Ru-Ir-Sb-Co electrode prepared by sequentially forming a TiN layer and an SiO2 layer on the surface of a titanium plate by magnetron sputtering and electrodeposition, and then coating a precursor by sol-gel method.
[0009] The electrocatalytic electrode is prepared by a method comprising the following steps:
[0010] Step 1: After polishing the titanium plate with sandpaper to a metallic shine, boil it in a 10% NaOH solution, then rinse it with clean water. Next, boil it in a 10% oxalic acid solution, rinse it with clean water, and then dry it to complete the etching process on the surface of the titanium plate.
[0011] Step 2: After the titanium plate with surface etching completed in Step 1 is coated by magnetron sputtering, it is then ultrasonically cleaned in acetone, ethanol and water for 10 min in sequence, then immersed in 0.5% HNO3 solution at room temperature for 30 s, rinsed with water and dried to obtain the titanium plate coated by magnetron sputtering.
[0012] Step 3: Using the titanium plate coated by magnetron sputtering in Step 2 as the working electrode and graphite as the counter electrode, electrodeposition is performed in the electrodeposition solution. After the electrodeposition treatment, it is immediately rinsed with clean water and then dried in a vacuum environment at 60~65℃ for 1.5~2 h. Then, it is heated to 250~300℃ in a N2 atmosphere at 1℃ / min, held at the temperature for 30 min, and then cooled to room temperature. In the plasma system, the vacuum degree is maintained at 10 Pa, the O2 / Ar volume ratio is 1:1, the total flow rate is 20 sccm, the processing power is 150 W, and after processing for 8 min, it is immersed in 0.5% HNO3 solution at room temperature for 30 s, then rinsed with clean water and dried with nitrogen to obtain the electrodeposited titanium plate.
[0013] Step 4: Apply the precursor evenly to the surface of the titanium plate that has been electrodeposited in Step 3, dry it, ignite it, and then anneal it naturally to room temperature;
[0014] Step 5: Repeat the process of step 4 12-16 times, rinse with clean water and anhydrous ethanol in sequence, and then blow dry with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0015] In step 1, the boiling temperature of the boiling treatment is 95-105℃ and the boiling time is 2-3 h; the micro-boiling temperature of the micro-boiling treatment is 80-90℃ and the micro-boiling time is 2.5-3 h.
[0016] In step 2, the process conditions for coating by magnetron sputtering are as follows:
[0017] The N2 / Ar flow ratio is 1:2-1:3, and the working pressure is 2×10⁻⁶. -4 Pa; sputtering power of 60-80 W, sputtering time of 1-1.5 h, and sputtering temperature of 400-500℃.
[0018] The electrodeposition solution in step 3 is prepared as follows: Tetramethoxysilane is dissolved in anhydrous ethanol to form solution A. Solution B, with an equal volume to solution A, is added dropwise to solution A. After stirring evenly, the pH is adjusted to 3 with dilute hydrochloric acid, and the reaction is carried out at 25°C for 5 hours to obtain the electrodeposition solution. Solution A is a 5% tetramethoxysilane-ethanol solution, and solution B is a 2% KNO3 aqueous solution.
[0019] In step 3, the electrodeposition process employs a constant current mode with a current density of 0.5~2 mA / cm². 2 The stirring rate was 200~300 r / min, the electrode spacing was 3 cm, the deposition time was 40~60 min, and the temperature was 25~40℃.
[0020] In step 4, the post-drying calcination refers to setting the drying temperature to 100-110℃ and the drying time to 20-30 min; and the calcination temperature to 500-700℃ and the calcination time to 20-30 min.
[0021] In step 4, the precursor is obtained through the following steps:
[0022] Step 4.1: Weigh out ruthenium source and iridium source in ethanol at a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5, and mix them evenly with ultrasonic stirring to obtain mixed solution C; the amount of ethanol used in this step is 1 / 3 of the total volume of ethanol used in the precursor preparation process.
[0023] Step 4.2: Weigh citric acid and ethylene glycol in ethanol at a molar ratio of M:citric acid:ethylene glycol = 1:4:15, and mix them evenly with ultrasonic stirring to obtain mixed solution D; add mixed solution D dropwise to mixed solution C, then add hydrochloric acid to adjust the pH to 2~2.5, and ultrasonically stir for 4 h to obtain mixed solution E; wherein: M refers to the sum of the molar numbers of ruthenium source and iridium source; the amount of ethanol used in this step is 1 / 3 of the total volume of ethanol used in the precursor preparation process.
[0024] Step 4.3: Weigh out antimony source and cobalt source in ethanol at a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5. After ultrasonic stirring to ensure homogeneity, add the mixture dropwise to the prepared solution E. Adjust the pH to 3.5-4.0 with NH4OH or HNO3, then ultrasonically stir for 1-2 hours to ensure homogeneity. Allow to stand for 36-40 hours to obtain the precursor. The amount of ethanol used in this step is 1 / 3 of the total volume of ethanol used in the precursor preparation process.
[0025] The ruthenium source is either ruthenium trichloride or ruthenium nitrate, or a mixture of the two in a 1:1 mass ratio.
[0026] The iridium source is either chloroiridic acid or iridium trichloride, or a mixture of the two in a 1:1 mass ratio.
[0027] The antimony source is either antimony trichloride or antimony acetate, or a mixture of the two in a 1:1 mass ratio.
[0028] The cobalt source is either cobalt nitrate or cobalt acetate, or a mixture of the two in a 1:1 mass ratio.
[0029] The concentration of the hydrochloric acid used to adjust the pH is 0.1 mol / L.
[0030] The concentrations of both NH4OH and HNO3 used to adjust the pH are 0.1 mol / L.
[0031] The application of the electrocatalytic electrode of this invention in the treatment of high-salt and high-ammonia-nitrogen wastewater.
[0032] Specifically, the TiN / SiO2 / Ru-Ir-Sb-Co electrode is used as the anode, and a stainless steel electrode is used as the cathode for water treatment of high-salt, high-ammonia-nitrogen wastewater, to remove NH4-N and Cl from the wastewater. - .
[0033] Regarding Cl - High-salt, high-ammonia-nitrogen wastewater with a concentration of 6000 mg / L and NH4-N of 600 mg / L, and a volume of 2 L, is treated using the following water treatment parameters: current density of 65 mA / cm³. 2With an electrode spacing of 2 cm, a stirring speed of 450 rpm, and a reaction time of 1.5 h, Cl was achieved. - The removal rate of NH4-N reaches over 95%.
[0034] Compared with the prior art, the beneficial effects of the present invention are reflected in:
[0035] 1. The electrocatalytic electrode of this invention exhibits excellent corrosion resistance, stability, and high catalytic activity, with strong resistance to impact loads. The TiN layer constructed by magnetron sputtering can suppress passivation of the titanium substrate, provide efficient electron transport, and improve its conductivity and corrosion resistance. The abundant silanol groups on the surface of the SiO2 electrodeposited layer can form strong chemical reactions with metal ions or hydrolysis products in the Ru-Ir-Sb-Co precursor, effectively suppressing coating cracking under high-temperature sintering or high current. Furthermore, the nanopores of the electrodeposited SiO2 provide the Ru-Ir-Sb-Co coating with an ultra-high specific surface area and increase its active site density. Ru-Ir provides efficient chlorine evolution reaction activity, and Sb-Co can enhance ammonia nitrogen oxidation capacity. The passivation layer formed by Sb can block Cl... - The erosion of active sites reduces electrode corrosion, extending its service life in high-salt environments.
[0036] 2. The electrocatalytic electrode of this invention maintains stable activity over a wide pH range, making it suitable not only for high-salt, high-ammonia-nitrogen wastewater, but also for acidic and alkaline industrial wastewater. It eliminates the need for acid or alkali adjustment, causes no secondary pollution, and avoids the chlorinated organic compounds produced by traditional breakpoint chlorination. Detailed Implementation
[0037] The present invention will be further described below. It should be noted that this embodiment is based on the present technical solution and provides detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to this embodiment.
[0038] Example 1:
[0039] This embodiment describes the preparation of a TiN / SiO2 / Ru-Ir-Sb-Co electrode, and the specific steps are as follows:
[0040] Step 1: After polishing the titanium plate (6 cm × 3 cm) with sandpaper to achieve a metallic shine, first boil it in a 10% NaOH solution at 105℃ for 2 hours, then take it out and wash it with clean water. Next, boil it in a 10% oxalic acid solution at 90℃ for 2.5 hours to perform surface etching, then wash it with clean water and blow it dry.
[0041] Step 2: After coating the etched titanium plate using magnetron sputtering, ultrasonically clean it for 10 min each in acetone, ethanol, and water, then immerse it in 0.5% HNO3 solution at room temperature for 30 s, rinse thoroughly with water, and dry it for later use. Magnetron sputtering conditions: N2 / Ar flow ratio 1:2.5, working gas pressure 2×10⁻⁶. -4 Pa, sputtering power of 80 W, sputtering time of 1.5 h, sputtering temperature of 450℃;
[0042] Step 3: Using the titanium plate treated in Step 2 as the working electrode and graphite as the counter electrode, electrodeposition was performed in the electrodeposition solution. After treatment, the plate was immediately rinsed with clean water and dried in a vacuum environment at 60℃ for 1.5 h. Then, in a N2 atmosphere, the temperature was increased to 300℃ at 1℃ / min, held at that temperature for 30 min, and then cooled to room temperature. The plasma system was maintained at a vacuum of 10 Pa, an O2 / Ar volume ratio of 1:1, a total flow rate of 20 sccm, and a processing power of 150 W for 8 min. After treatment, the plate was immersed in 0.5% HNO3 solution at room temperature for 30 s, immediately rinsed with clean water, and dried with nitrogen. The electrodeposition solution was prepared as follows: tetramethoxysilane was dissolved in anhydrous ethanol to form a 5% tetramethoxysilane-ethanol solution. An equal volume of 2% KNO3 aqueous solution was then added dropwise. After stirring evenly, the pH of the solution was adjusted to 3 with dilute hydrochloric acid. The reaction was carried out at 25℃ with stirring for 5 h. Electrodeposition was performed in constant current mode with a current density of 1.5 mA / cm². 2 The stirring rate was 280 r / min, the electrode spacing was 3 cm, the deposition time was 50 min, and the temperature was 30℃.
[0043] Step 4: The precursor is evenly coated on the surface of the titanium plate after step 3, dried at 105℃ for 20 min, calcined at 650℃ for 30 min, and naturally annealed to room temperature. This process is repeated 15 times. After rinsing with clean water and anhydrous ethanol, the plate is dried with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0044] The precursor is obtained through the following steps:
[0045] 1) Weigh out ruthenium trichloride and chloroiridic acid in a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5 and dissolve them in 1 / 3 volume of ethanol solution. Stir ultrasonically to mix them evenly.
[0046] 2) Weigh out citric acid and ethylene glycol in a molar ratio M (ruthenium trichloride and chloroiridic acid):citric acid:ethylene glycol = 1:4:15 and dissolve them in 1 / 3 of the total volume of ethanol solution. After ultrasonic stirring to mix them evenly, slowly add the mixed solution dropwise to the mixed solution in 1), and add water and 0.1 mol / L hydrochloric acid in a volume ratio of 1:1. Stir ultrasonically for 4 h.
[0047] 3) Weigh antimony trichloride and cobalt nitrate in an ethanol solution with a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5. Dissolve them in 1 / 3 volume of the total volume of ethanol solution. Stir the solution with ultrasound until it is homogeneous. Then slowly add the solution dropwise to the mixture in step 2). Adjust the pH to 3.5 with 0.1 mol / L NH4OH / HNO3. Stir the solution with ultrasound for 2 hours until it is homogeneous. Let it stand for 38 hours before use to obtain the precursor.
[0048] The TiN / SiO2 / Ru-Ir-Sb-Co electrode prepared in Example 1 was used as the anode, and a stainless steel electrode was used as the cathode in 2 L of high-salt, high-ammonia-nitrogen wastewater (Cl). - In a concentration of 6000 mg / L (NH4-N = 600 mg / L), the current density is 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ 535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 1 below.
[0049] Example 2:
[0050] This embodiment describes the preparation of a SiO2 / Ru-Ir-Sb-Co electrode, and the specific steps are as follows:
[0051] Step 1: After polishing the titanium plate (6 cm × 3 cm) with sandpaper to bring out the metallic luster, first put it into a 10% NaOH solution and boil it at 100℃ for 2.5 h, then take it out and wash it with clean water. Then put it into a 10% oxalic acid solution and boil it at 85℃ for 3 h to perform surface etching. After washing it with clean water, blow it dry.
[0052] Step 2: Using the etched titanium plate as the working electrode and graphite as the counter electrode, electrodeposition was performed in the electrodeposition solution. After treatment, the plate was immediately rinsed with clean water and dried in a vacuum environment at 65℃ for 2 h. Then, in a N2 atmosphere, the temperature was increased to 300℃ at 1℃ / min, held for 30 min, and cooled to room temperature. The plasma system was maintained at a vacuum of 10 Pa, an O2 / Ar volume ratio of 1:1, a total flow rate of 20 sccm, and a processing power of 150 W for 8 min. After treatment, the plate was immersed in 0.5% HNO3 solution at room temperature for 30 s, immediately rinsed with clean water, and dried with nitrogen. The electrodeposition solution was prepared as follows: tetramethoxysilane was dissolved in anhydrous ethanol to form a 5% tetramethoxysilane-ethanol solution. An equal volume of 2% KNO3 aqueous solution was then added dropwise. After stirring, the pH of the solution was adjusted to 3 with dilute hydrochloric acid. The reaction was carried out at 25℃ with stirring for 5 h. Electrodeposition was performed in a constant current mode with a current density of 2 mA / cm². 2 The stirring rate was 300 r / min, the electrode spacing was 3 cm, the deposition time was 60 min, and the temperature was 35℃.
[0053] Step 3: The precursor is evenly coated on the surface of the titanium plate after step 2, dried at 100℃ for 25 min, calcined at 600℃ for 30 min, and naturally annealed to room temperature. This process is repeated 13 times. After rinsing with clean water and anhydrous ethanol in sequence, the plate is dried with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0054] The precursor is obtained through the following steps:
[0055] 1) Weigh out ruthenium trichloride and chloroiridic acid in a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5 and dissolve them in 1 / 3 volume of ethanol solution. Stir ultrasonically to mix them evenly.
[0056] 2) Weigh out citric acid and ethylene glycol in a molar ratio M (ruthenium trichloride and chloroiridic acid):citric acid:ethylene glycol = 1:4:15 and dissolve them in 1 / 3 of the total volume of ethanol solution. After ultrasonic stirring to mix them evenly, slowly add the mixed solution dropwise to the mixed solution in 1), and add water and 0.1 mol / L hydrochloric acid in a volume ratio of 1:1. Stir ultrasonically for 4 h.
[0057] 3) Weigh antimony trichloride and cobalt nitrate in an ethanol solution with a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5. Dissolve them in 1 / 3 volume of the total volume of ethanol solution. Stir the solution with ultrasound until it is homogeneous. Then slowly add the solution dropwise to the mixture in step 2). Adjust the pH to 3.5 with 0.1 mol / L NH4OH / HNO3. Stir the solution with ultrasound for 2 hours until it is homogeneous. Let it stand for 38 hours before use to obtain the precursor.
[0058] The SiO2 / Ru-Ir-Sb-Co electrode prepared in Example 2 was used as the anode, and a stainless steel electrode was used as the cathode. The electrode was placed in 2 L of high-salt, high-ammonia-nitrogen wastewater (Cl...). - In a concentration of 6000 mg / L (NH4-N = 600 mg / L), the current density is 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ 535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 1 below.
[0059] Example 3:
[0060] This embodiment describes the preparation of a Ru-Ir-Sb-Co electrode, and the specific steps are as follows:
[0061] Step 1: After polishing the titanium plate (6 cm × 3 cm) with sandpaper to achieve a metallic shine, first boil it in a 10% NaOH solution at 105℃ for 2 hours, then take it out and wash it with clean water. Next, boil it in a 10% oxalic acid solution at 90℃ for 2.5 hours to perform surface etching, then wash it with clean water and blow it dry.
[0062] Step 2: The precursor is evenly coated on the etched titanium plate surface, dried at 105℃ for 20 min, calcined at 650℃ for 30 min, and naturally annealed to room temperature. This process is repeated 15 times. After rinsing with water and anhydrous ethanol, the plate is dried with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0063] The precursor is obtained through the following steps:
[0064] 1) Weigh out ruthenium trichloride and chloroiridic acid in a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5 and dissolve them in 1 / 3 volume of ethanol solution. Stir ultrasonically to mix them evenly.
[0065] 2) Weigh out citric acid and ethylene glycol in a molar ratio M (ruthenium trichloride and chloroiridic acid):citric acid:ethylene glycol = 1:4:15 and dissolve them in 1 / 3 of the total volume of ethanol solution. After ultrasonic stirring to mix them evenly, slowly add the mixed solution dropwise to the mixed solution in 1), and add water and 0.1 mol / L hydrochloric acid in a volume ratio of 1:1. Stir ultrasonically for 4 h.
[0066] 3) Weigh antimony trichloride and cobalt nitrate in an ethanol solution with a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5. Dissolve them in 1 / 3 volume of the total volume of ethanol solution. Stir the solution with ultrasound until it is homogeneous. Then slowly add the solution dropwise to the mixture in step 2). Adjust the pH to 3.5 with 0.1 mol / L NH4OH / HNO3. Stir the solution with ultrasound for 2 hours until it is homogeneous. Let it stand for 38 hours before use to obtain the precursor.
[0067] The Ru-Ir-Sb-Co electrode prepared in Example 3 was used as the anode, and a stainless steel electrode was used as the cathode. The electrode was placed in 2 L of high-salt, high-ammonia-nitrogen wastewater (Cl...). - In a concentration of 6000 mg / L (NH4-N = 600 mg / L), the current density is 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 1 below.
[0068] Example 4:
[0069] This embodiment describes the preparation of a Ru-Ir-Co electrode, and the specific steps are as follows:
[0070] Step 1: After polishing the titanium plate (6 cm × 3 cm) with sandpaper to bring out the metallic luster, first put it into a 10% NaOH solution and boil it at 100℃ for 2.5 h, then take it out and wash it with clean water. Then put it into a 10% oxalic acid solution and boil it at 85℃ for 3 h to perform surface etching. After washing it with clean water, blow it dry.
[0071] Step 2: The precursor is evenly coated on the etched titanium plate surface, dried at 100℃ for 25 min, calcined at 600℃ for 30 min, and naturally annealed to room temperature. This process is repeated 13 times. After rinsing with clean water and anhydrous ethanol in sequence, the plate is dried with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0072] The precursor is obtained through the following steps:
[0073] 1) Weigh out ruthenium trichloride and chloroiridic acid in a molar ratio of Ru:Ir:Co = 1:1:0.5 and dissolve them in 1 / 3 of the total volume of ethanol solution. Stir ultrasonically to mix them evenly.
[0074] 2) Weigh out citric acid and ethylene glycol in a molar ratio M (ruthenium trichloride, chloroiridic acid):citric acid:ethylene glycol = 1:4:15 and dissolve them in 1 / 3 volume of ethanol solution. After ultrasonic stirring to mix them evenly, slowly add the mixed solution dropwise to the mixed solution in 1), and add water and 0.1 mol / L hydrochloric acid in a volume ratio of 1:1. Stir ultrasonically for 4 h.
[0075] 3) Weigh out cobalt nitrate in 1 / 3 volume of ethanol solution according to the molar ratio Ru:Ir:Co=1:1:0.5, stir it with ultrasonication until it is evenly mixed, and then slowly add it dropwise to the mixed solution in 2). Adjust the pH to 3.5 with 0.1 mol / L NH4OH / HNO3, stir it with ultrasonication for 2 h until it is evenly mixed, and let it stand for 38 h before use to obtain the precursor.
[0076] The Ru-Ir-Co electrode prepared in Example 4 was used as the anode, and the stainless steel electrode was used as the cathode. The mixture was placed in 2 L of high-salt, high-ammonia-nitrogen wastewater (Cl...). - In a concentration of 6000 mg / L (NH4-N = 600 mg / L), the current density is 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ 535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 1 below.
[0077] Example 5:
[0078] This embodiment describes the preparation of a Ru-Ir electrode, and the specific steps are as follows:
[0079] Step 1: After polishing the titanium plate (6 cm × 3 cm) with sandpaper to bring out the metallic luster, first put it into a 10% NaOH solution and boil it at 105℃ for 2.5 h, then take it out and wash it with clean water. Then put it into a 10% oxalic acid solution and boil it at 90℃ for 3 h to perform surface etching. After washing it with clean water, blow it dry.
[0080] Step 2: The precursor is evenly coated on the etched titanium plate surface, dried at 100℃ for 25 min, calcined at 600℃ for 30 min, and naturally annealed to room temperature. This process is repeated 13 times. After rinsing with clean water and anhydrous ethanol in sequence, the plate is dried with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater.
[0081] The precursor is obtained through the following steps:
[0082] 1) Weigh out ruthenium trichloride and chloroiridic acid in a molar ratio Ru:Ir=1:1 and dissolve them in 1 / 3 of the total volume of ethanol solution. Stir ultrasonically to mix them evenly.
[0083] 2) Weigh out citric acid and ethylene glycol in a molar ratio M (ruthenium trichloride and chloroiridic acid):citric acid:ethylene glycol = 1:4:15 and dissolve them in 1 / 3 volume of ethanol solution. After ultrasonic stirring to ensure uniform mixing, slowly add this mixture dropwise to the mixture in 1). Then add water and 0.1 mol / L hydrochloric acid in a volume ratio of 1:1. Adjust the pH to 3.5 with 0.1 mol / L NH4OH / HNO3. Ultrasonic stir for 2 hours to ensure uniform mixing. Let stand for 38 hours before use to obtain the precursor.
[0084] The Ru-Ir electrode prepared in Example 5 was used as the anode, and the stainless steel electrode was used as the cathode, placed in 2 L of high-salt, high-ammonia-nitrogen wastewater (Cl). - In a concentration of 6000 mg / L (NH4-N = 600 mg / L), the current density is 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ 535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 1 below.
[0085]
[0086] The results in the table above show that the TiN / SiO2 / Ru-Ir-Sb-Co quaternary electrocatalytic electrode prepared in Example 1 can effectively remove NH4-N and Cl from wastewater. - Its electrocatalytic activity is far higher than that of the electrode prepared in the comparative example. TiN / SiO2 can effectively block Cl. - corrosion.
[0087] A 3 mol / L NaCl solution was prepared as the electrolyte for electrocatalysis, and a 1 mol / L H₂SO₄ solution was added to adjust the pH of the electrolyte. Electrodes prepared in Examples 1-5 were used as anodes, and stainless steel plates as cathodes, at a current density of 2 A / cm². 2 Under the specified conditions, accelerated lifetime testing was performed on the electrocatalytic electrode, and the test results are shown in Table 2 below.
[0088]
[0089] The results in the table above show that at a current density of 2 A / cm², 2In a strong acid and high salt environment, the TiN / SiO2 / Ru-Ir-Sb-Co electrocatalytic electrode prepared in Example 1 still exhibits significant durability; however, the lack of a TiN layer leads to uneven local current density, the lack of a TiN / SiO2 layer makes the coating prone to peeling at high current densities, and the absence of Sb doping exacerbates Cl... - Adsorption accelerates corrosion, and the formation of a TiO2 insulating layer on the surface of a single Ti plate will shorten the lifespan of its electrodes.
[0090] The electrodes prepared in Examples 1-5 were used as anodes, and the stainless steel electrode was used as cathodes, placed in 2L of high-salt, high-ammonia-nitrogen wastewater (Cl... - In a solution containing 6000 mg / L of sodium hydroxide and 600 mg / L of NH4-N, the initial pH values were adjusted to 4, 7, and 10, and the current density was 65 mA / cm². 2 The electrode spacing was 2 cm, the stirring speed was 450 rpm, and the reaction was carried out for 1.5 h. The concentrations of NH4-N and Cl in the wastewater were then measured. - Value (NH4-N detection method refers to "HJ 535-2009", Cl) - The detection method for the value is in accordance with GB / T 15453-2018, and the detection results are shown in Table 3 below.
[0091]
[0092] The results in the table above show that the TiN / SiO2 / Ru-Ir-Sb-Co electrocatalytic electrode prepared in Example 1 maintains stable activity over a wide pH range and can efficiently remove NH4-N and Cl from wastewater. - The value is such that no acidity or alkali adjustment is needed.
[0093] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. An electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater, characterized in that: The electrocatalytic electrode is a TiN / SiO2 / Ru-Ir-Sb-Co electrode prepared by sequentially forming a magnetron sputtered TiN layer and an electrodeposited SiO2 layer on the surface of a titanium plate, and then coating the precursor by sol-gel method. The electrocatalytic electrode is prepared by a method comprising the following steps: Step 1: After polishing the titanium plate with sandpaper to a metallic shine, boil it in a 10% NaOH solution, then rinse it with clean water. Next, boil it in a 10% oxalic acid solution, rinse it with clean water, and then dry it to complete the etching process on the surface of the titanium plate. Step 2: After the titanium plate with surface etching completed in Step 1 is coated by magnetron sputtering, it is then ultrasonically cleaned in acetone, ethanol and water for 10 min in sequence, and then immersed in 0.5% HNO3 solution at room temperature for 30 s, rinsed with water and dried to obtain the titanium plate coated by magnetron sputtering. Step 3: Using the titanium plate coated by magnetron sputtering in Step 2 as the working electrode and graphite as the counter electrode, electrodeposition is performed in the electrodeposition solution. After the electrodeposition treatment, the plate is immediately rinsed with clean water and then dried in a vacuum environment at 60~65℃ for 1.5~2 h. Subsequently, the plate is heated to 250~300℃ in a N2 atmosphere and held at that temperature for 30 min before being cooled to room temperature and removed. In the plasma system, the vacuum degree is maintained at 10 Pa, the O2 / Ar volume ratio is 1:1, the total flow rate is 20 sccm, the processing power is 150 W, and the treatment is carried out for 8 min. After treatment, the plate is immersed in 0.5% HNO3 solution at room temperature for 30 s, then rinsed with clean water and dried with nitrogen to obtain the electrodeposited titanium plate. Step 4: Apply the precursor evenly to the surface of the titanium plate that has been electrodeposited in Step 3, dry it, ignite it, and then anneal it naturally to room temperature; Step 5: Repeat the process of step 4 12-16 times, rinse with clean water and anhydrous ethanol in sequence, and then blow dry with nitrogen to obtain the electrocatalytic electrode for the treatment of high-salt and high-ammonia nitrogen wastewater. In step 4, the precursor is obtained through the following steps: Step 4.1: Weigh out ruthenium source and iridium source in ethanol at a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5, and mix them evenly with ultrasonic stirring to obtain mixed solution C. Step 4.2: Weigh out citric acid and ethylene glycol in ethanol at a molar ratio of M:citric acid:ethylene glycol = 1:4:15, and mix them evenly with ultrasonic stirring to obtain mixed solution D; add mixed solution D dropwise to mixed solution C, then add hydrochloric acid to adjust the pH value to obtain a mixed solution with a pH of 2~2.5, and then stir ultrasonically for 4 hours to obtain mixed solution E; wherein, M refers to the sum of the molar numbers of ruthenium source and iridium source; Step 4.3: Weigh out the antimony source and cobalt source in ethanol at a molar ratio of Ru:Ir:Sb:Co = 1:1:0.5:0.5, stir ultrasonically to mix them evenly, then drop them into the mixed solution E, adjust the pH to 3.5-4.0, stir ultrasonically for 1-2 hours to mix evenly, and then let it stand for 36-40 hours to obtain the precursor.
2. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: In step 1, the boiling temperature for the boiling treatment is 95-105℃ and the boiling time is 2-3 h; the micro-boiling temperature for the micro-boiling treatment is 80-90℃ and the micro-boiling time is 2.5-3 h.
3. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: In step 2, the process conditions for coating by magnetron sputtering are as follows: The N2 / Ar flow ratio is 1:2-1:3; The sputtering power is 60-80 W, the sputtering time is 1-1.5 h, and the sputtering temperature is 400-500℃.
4. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: In step 3, the electrodeposition solution is prepared as follows: tetramethoxysilane is dissolved in anhydrous ethanol to form solution A, and solution B of the same volume as solution A is added dropwise to solution A. After stirring evenly, the pH is adjusted to 3 with dilute hydrochloric acid, and then the reaction is stirred at 25°C for 5 h to obtain the electrodeposition solution. Solution A is a 5% (w / w) tetramethoxysilane-ethanol solution. Solution B is a 2% KNO3 aqueous solution.
5. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: In step 3, the electrodeposition process employs a constant current mode with a current density of 0.5~2 mA / cm². 2 The stirring rate was 200~300 r / min, the electrode spacing was 3 cm, the deposition time was 40~60 min, and the temperature was 25~40℃.
6. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: In step 4, the calcination after drying refers to: drying temperature of 100-110℃ and drying time of 20-30 min; calcination temperature of 500-700℃ and calcination time of 20-30 min.
7. The electrocatalytic electrode for treating high-salt, high-ammonia-nitrogen wastewater according to claim 1, characterized in that: The ruthenium source is either ruthenium trichloride or ruthenium nitrate, or a mixture of the two in a 1:1 mass ratio. The iridium source is either chloroiridic acid or iridium trichloride, or a mixture of two of them in a 1:1 mass ratio. The antimony source is either antimony trichloride or antimony acetate, or a mixture of the two in a mass ratio of 1:
1. The cobalt source is either cobalt nitrate or cobalt acetate, or a mixture of the two in a 1:1 mass ratio.
8. The application of the electrocatalytic electrode according to any one of claims 1-7 in the treatment of high-salt, high-ammonia-nitrogen wastewater, characterized in that: Using the TiN / SiO2 / Ru-Ir-Sb-Co electrode as the anode and a stainless steel electrode as the cathode, an electrochemical treatment was performed on high-salt, high-ammonia-nitrogen wastewater to remove NH4-N and Cl from the wastewater. - .
Citation Information
Patent Citations
Electrode material for electrocatalytic degradation of organic wastewater containing high-concentration nitrate and application of electrode material
CN119591204A
Ruthenium-iridium-tin-cobalt mixed noble metal coating anode material and preparation method thereof
CN118241242A
Anode material, preparation method, electrolysis device and application thereof
CN120485836A